SHROOM3 IN THE KIDNEY - Khalili, Hadiseh (My University, 2015)
Chronic kidney disease (CKD), defined as an irreversible reduction in glomerular filtration rate, is a large public health concern. Dissecting the genetic components of CKD is required to improve our understanding of disease pathogenesis. Researchers have identified that SHROOM3, has very high associations with kidney disease and function. Shroom3 encodes an actin-binding protein important in regulating cell and tissue morphogenesis. However, there is a lack of evidence supporting a role for Shroom3 in kidney function or disease. Here, I investigated the developmental and functional role of Shroom3 in the mammalian kidney. For the first time, I described the expression pattern of Shroom3 in the embryonic and adult mouse kidneys. By performing in situ hybridization and immunohistochemistry, I demonstrated that Shroom3 is expressed in the condensing mesenchyme, podocytes, and collecting ducts. I further showed that Shroom3 protein is localized in the foot processes of podocytes, utilizing immunogold labeling and transmission electron microscopy. In order to uncover a potential role of Shroom3 in the kidney, we utilized Shroom3 knockout mice. Shroom3 mutants demonstrated marked glomerular abnormalities including cystic and degenerating glomeruli, and reduced glomerular number. Scanning and transmission electron microscopic analyses of Shroom3 mutant glomeruli revealed disruptions in podocyte morphology characterized by disorganized foot processes with less interdigitation and segmental foot processes effacement. Furthermore, immunofluorescence analysis of mutant kidneys revealed aberrant distribution of podocyte actin-associated proteins. Elucidating the underlying molecular mechanism of this abnormal podocyte architecture; v we demonstrated that in the absence of Shroom3, Rho kinase is mislocalized in the apical membrane of podocytes. As a result, mislocalized Rho kinase failed to phosphorylate non-muscle myosin and induce actomyosin contraction resulting in a patchy granular distribution of actin in the podocytes of Shroom3 mutants. Taken together, our findings established that Shroom3 is essential for proper actin organization in the podocytes through interaction with Rock. Furthermore, we took advantage of a haploinsufficiency phenotype of Shroom3 heterozygote adult mice and demonstrated these mice develop glomerulosclerosis and proteinuria. In conclusion, our studies provided evidence to support a role for Shroom3 in kidney development and disease and support the GWAS studies that suggested a correlation between SHROOM3 variants and kidney function in humans.
SHROOM3 PLAYS A ROLE IN PODOCYTE CYTOARCHITECTURE
Keywords: Kidney; Glomerulus; Podocyte; Shroom3; CKD; Kidney Development